Are cross-border worker protections under challenge? Insights from a comparative perspective between Italy and the Netherlands - Russo, Marianna (Diritto Pubblico Europeo - Rassegna online, 2024)
Is it possible to take the principle of the free movement of workers within the EU for granted? This paper aims to identify the most insidious challenges and the most effective remedies to guarantee the principle of equal treatment and non-discrimination on grounds of nationality. It does so by analysing regulatory frameworks, case law and data on cross-border workers from European and comparative perspectives, with special focus on Italy and the Netherlands.